Hepatic Candidiasis in an Immunocompetent Woman: A Rare Complication of Pylephlebitis. Issue 3 (May 2019) - Gottlieb, Lindsey B.; Hashemi, Alexandra; Dewar, Robert; Salama, Carlos
Abstract : Abstract: Pylephlebitis, or portal vein thrombus infection, is a rare condition that is often missed owing to the nonspecific nature of its signs and symptoms and an underappreciation of the clinical entity. Causative microbes are typically bacteria, although cases of candidal pylephlebitis have been described. Given the invasive technique required to culture the portal vein, antimicrobial selection typically relies on the assumption that the microbes isolated in blood culture are the same as those infecting the portal vein thrombus. We present a case of pylephlebitis in an immunocompetent patient with viridans streptococci and Bacteroides fragilis bacteremia subsequently found to have associated hepatic Candida abscesses. Our case highlights the need to proceed with caution when narrowing antimicrobial therapy for patients with pylephlebitis based on blood culture data alone. It also represents a rare exception to the teaching that hepatic Candida abscesses are only seen in individuals who are profoundly immunocompromised.